Electrode grid line preparation method and photovoltaic cell

Through the two-layer conductive paste structure and mold imprinting technology, the accuracy, efficiency and cost problems in the photovoltaic cell electrode gate line printing technology are solved, and high-performance and low-cost electrode manufacturing is achieved, which meets high efficiency and large-scale production demand.

CN119208452APending Publication Date: 2024-12-27BEIJING ZENITHNANO TECH CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411372309.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing photovoltaic cell electrode gate line printing technology has challenges in terms of accuracy, efficiency and cost, and it is difficult to meet the needs of high-performance and high-performance batteries. The traditional screen printing process leads to waste of materials and high production costs.

Method used

Using two-layer conductive paste structure and mold imprinting technology, the high-resolution electrode pattern is achieved through transfer and sintering of the polymer layer, and the combination of heat and pressure ensures good contact and bond between materials, reducing Waste production and environmental pollution.

Benefits of technology

It improves the conductivity, stability and performance of the electrode, reduces production costs, extends the service life of the electrode, meets the needs of large-scale production, and enhances market competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208452A_ABST
    Figure CN119208452A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode grid line preparation method and a photovoltaic cell, and relates to the field of photovoltaic technology, and the method comprises the following steps: S1, providing a substrate, and forming a polymer layer on the substrate; s2, providing a first mold, and pressing a first groove on the polymer layer; s3, first conductive slurry is smeared on the polymer layer; s4, providing a second mold, and pressing a second groove on the first conductive slurry; s5, smearing second conductive slurry on the first conductive slurry; s6, providing a base material, and transferring the first conductive slurry and the second conductive slurry onto the base material; s7, stripping the substrate, dissolving the polymer layer, and enabling the first conductive slurry and the second conductive slurry to be adhered to the base material; and S8, sintering the first conductive slurry and the second conductive slurry to form the electrode grid line. By adopting a combined structure of the first conductive slurry and the second conductive slurry, the cost can be reduced while the conductive effect of the electrode grid line is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photovoltaic technology, and in particular to a method for preparing an electrode grid line and a photovoltaic cell. Background Art

[0002] The electrode grid printing technology of photovoltaic cells is a crucial part of its production process, which directly affects the energy conversion efficiency and production cost of the battery. At present, the widely used electrode grid printing technologies include screen printing, inkjet printing, offset printing and flexible printing. Among them, screen printing has become the most commonly used printing method due to its mature process and popular equipment. This technology prints silver paste onto the surface of photovoltaic cells through a screen to form an electrode pattern, thereby achieving effective collection and conduction of electrical energy.

[0003] Although screen printing technology plays an important role in the production of solar cells, its accuracy is limited by the aperture of the screen and the printing pressure, which makes it difficult to print fine patterns and high resolution. This limitation reduces the flexibility of electrode design and cannot meet the needs of higher efficiency and higher performance batteries. In addition, a certain amount of waste will be generated during the screen printing process, resulting in material waste, and the service life of the screen is limited, and the maintenance and replacement costs are high. These factors together lead to the high overall production cost of screen printing. At the same time, screen printing, as a relatively slow production process, is difficult to meet the efficiency requirements of large-scale production, thus limiting the output and market competitiveness of solar cells.

[0004] In terms of electrode performance, solar cells require electrodes to have good conductivity, appropriate grid line plasticity and low silicon wafer contact resistance. However, most of the current technologies still rely on a single conductive material, silver paste, which not only leads to high production costs, but also appears to be insufficient in terms of economy.

[0005] In summary, the current silver paste grid printing technology for photovoltaic cells faces multiple challenges such as accuracy, efficiency and cost. In order to improve battery performance and market competitiveness, it is urgent to explore new technologies to meet the needs of the modern photovoltaic industry for high-efficiency and low-cost batteries. Summary of the invention

[0006] In order to reduce the manufacturing cost of photovoltaic cell electrodes and improve production efficiency and quality, the present application provides an electrode grid line preparation method and a photovoltaic cell.

[0007] The present application provides an electrode grid line preparation method and a photovoltaic cell using the following technical solutions: A method for preparing an electrode grid line comprises the following steps: S1, providing a substrate, forming a polymer layer on the substrate; S2, providing a first mold, using the first mold to press a first groove corresponding to a desired electrode pattern on the polymer layer; S3, applying a first conductive paste on the polymer layer, so that the first conductive paste fills the first groove, and scraping off excess of the first conductive paste; S4, providing a second mold, using the second mold to press a second groove on the first conductive paste, and drying the first conductive paste; S5, applying a second conductive paste on the first conductive paste, so that the second conductive paste fills the first groove; Fill the second groove with conductive paste, and scrape off the excess second conductive paste; S6, provide a substrate, cover the polymer layer on the substrate, and transfer the polymer layer, the first conductive paste and the second conductive paste to the substrate at a certain temperature and pressure. At the same time, the second conductive paste is dried and shaped to enhance the adhesion to the surface of the substrate; S7, peel off the base and the polymer layer, and dissolve the polymer layer, leaving the first conductive paste and the second conductive paste adhered to the substrate; S8, sinter the first conductive paste and the second conductive paste to form the electrode grid line.

[0008] By adopting the above technical solution, the present application adopts a two-layer conductive paste structure, which helps to improve the conductivity, stability and performance of the electrode, so that the electrode exhibits better electrical characteristics in practical applications; by using a mold to press a groove on the polymer layer, the pressure and temperature in the transfer process ensure that the first conductive paste and the second conductive paste are accurately transferred and attached to the substrate, maintaining the accuracy of the electrode pattern, achieving high-resolution and high-precision electrode pattern manufacturing, ensuring the accuracy and repeatability of the electrode structure, and meeting the strict requirements of optoelectronic devices on electrode shape and size; the process integrates multiple steps together, through flat coating technology, transfer, water dissolution, drying, high-temperature sintering Technologies such as the above reduce the complex processes in traditional manufacturing methods, improve production efficiency, and reduce manufacturing costs. Through the combination of heat and pressure, good contact and bonding between different materials are ensured, which is beneficial to improving the adhesion of the conductive paste on the substrate, ensuring that the electrode is not easy to fall off during long-term use, enhancing the overall performance of the electrode, and extending the service life of the device; and the use of the polymer layer can be removed by dissolution in subsequent steps, which helps to reduce the waste generated in traditional processes and reduce environmental pollution; compared with the traditional screen printing method, the present application can improve the production rate to a certain extent, meet the needs of large-scale production, and thus improve market competitiveness.

[0009] In a specific embodiment, the thickness of the polymer layer is 5-20 μm, and the opening width of the electrode pattern is 3-10 μm.

[0010] By adopting the above technical solution, the above dimensions can take into account the subsequent filling efficiency of the conductive paste and the requirements for the dimensional accuracy of the electrode grid lines. The opening width design ensures that the conductive paste can be fully and evenly filled to avoid the generation of voids and defects. The narrower opening width helps to reduce the parasitic resistance between the electrode grid lines, thereby improving the current collection efficiency of the battery. By precisely controlling the thickness of the polymer layer and the width of the patterned opening, the dimensional accuracy of the formed electrode grid lines can be significantly improved, which helps to reduce performance fluctuations and defective product rates caused by dimensional deviations.

[0011] In a specific embodiment, the glass transition temperature of the polymer layer is 70-100° C., and the material of the polymer layer is a water-soluble polymer material.

[0012] By adopting the above technical solution and utilizing the glass transition temperature of the polymer layer of 70-100°C, it is ensured that the material maintains good mechanical properties and structural stability at a suitable operating temperature. The moderate glass transition temperature minimizes the thermal damage to other sensitive materials during processing. At the same time, the conductive paste can be dried simultaneously at this processing temperature, and the transfer and drying can be carried out simultaneously. The design of water-soluble polymer materials improves the processing convenience and environmental friendliness, reduces the use of organic solvents, and reduces production costs.

[0013] In a specific embodiment, the water-soluble polymer material is one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, and polyvinyl alcohol-polyacrylonitrile.

[0014] By adopting the above technical solution, the above material has good compatibility with a variety of substrates and other polymer materials, which helps to improve the adhesion and interoperability between different materials, and has good film-forming properties and fluidity, so that it is easy to form during the production process and facilitate the preparation of parts with complex shapes; the above material can provide good strength and flexibility under certain conditions, ensuring the durability and reliability of the final product, and is generally environmentally friendly during use and handling, helping to reduce environmental pollution and waste of resources.

[0015] In a specific embodiment, the contact resistance of the second conductive paste is smaller than the contact resistance of the first conductive paste, and the conductivity of the second conductive paste is greater than the conductivity of the first conductive paste.

[0016] By adopting the above technical solution, the second conductive paste is used as the material in direct contact with the substrate. The low contact resistance and high conductivity of the second conductive paste can improve the connection performance between the substrate and the electrode, ensuring that the current can flow smoothly through each contact point. The good electrical properties help to improve the overall reliability of the equipment and avoid performance degradation or failure due to poor contact.

[0017] In a specific implementation manner, the second conductive paste is silver paste, and the first conductive paste is one of aluminum paste, copper paste, chromium paste, tin paste, indium paste, nickel paste, titanium paste, and tantalum paste.

[0018] By adopting the above technical solution, by limiting the silver paste to the area in contact with the substrate, the amount of silver paste used can be significantly reduced, and the conductive efficiency of the overall circuit can still be guaranteed; combining silver paste with other lower-cost conductive pastes can not only reduce production costs, but also bring technical advantages in improving product performance, ensuring conductive efficiency and improving mechanical strength.

[0019] In a specific embodiment, the silver paste comprises a binder, and the binder is a phenolic resin or an epoxy resin.

[0020] By adopting the above technical scheme and using phenolic resin or epoxy resin as a component of silver paste, the adhesion of silver paste on the surface of the substrate can be significantly improved, ensuring that the silver paste is firmly adhered to the circuit or other substrates to prevent falling off or peeling; not only the performance stability and durability of the silver paste are enhanced, but also good conductivity, adhesion and environmental adaptability are ensured.

[0021] In a specific implementation manner, the width of the first groove is the same as the width of the second groove, and the ratio of the height of the first groove to the height of the second groove is 2:1-5:1.

[0022] By adopting the above technical solution, the design of the same width ensures a good connection between the two conductive layers, which helps to improve the conductivity and stability of the electrode; the design of the height ratio of 2:1-5:1 reduces the amount of silver paste required by controlling the height of the second groove. Although the thickness of the silver paste is reduced, due to the high conductivity of the second conductive paste, the desired conductive effect can still be achieved, while reducing the overall production cost.

[0023] In a specific embodiment, the material of the substrate includes one of polyethylene terephthalate, polyimide, polyethylene terephthalate copolymer, polycarbonate, polypropylene, and polyurethane, and the thickness of the substrate is 100-200 μm.

[0024] By adopting the above technical solution, the above materials all have excellent mechanical properties and durability, can provide sufficient supporting force, and enhance the compression, bending and impact resistance of the entire structure; the thickness of 100-200μm provides good rigidity for the substrate while maintaining a certain flexibility, so that the material has strong adaptability in application and can be deformed within a certain range without breaking.

[0025] In a specific possible implementation manner, the longitudinal cross-sectional shape of the first groove and the second groove is one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, and a polygon.

[0026] By adopting the above technical solution and designing a variety of shapes, in actual production, the appropriate groove shape can be selected according to specific technical requirements and design goals, thereby playing an important role in enhancing product functions, improving stability and reducing costs.

[0027] In a specific implementation manner, the first groove and the second groove are formed by hot pressing at a temperature of 90-150°C.

[0028] By adopting the above technical solution and performing hot pressing molding at a hot pressing temperature of 90-150°C, the first groove and the second groove can be formed efficiently, accurately and firmly, ensuring that the geometric shapes of the first and second grooves meet the design requirements. The hot pressing molding process can achieve rapid molding under good temperature control and improve production efficiency.

[0029] In a specific possible implementation manner, in S4, after the second groove is pressed out, the first conductive paste is dried at a temperature of 100-200° C.

[0030] By adopting the above technical solution, by drying the first conductive paste at a temperature of 100-200°C, the molding effect of the second groove can be effectively ensured, thereby creating ideal conditions for the subsequent filling of the second conductive paste; the surface of the completely dried first conductive paste layer will be drier and smoother, which is conducive to the good adhesion of the second conductive paste. This surface condition can avoid the formation of bubbles, enhance the bonding force between the two conductive pastes, ensure the subsequent filling is uniform, and ensure the interoperability and functionality between the two pastes.

[0031] In a specific possible implementation manner, in S6, the first conductive paste and the second conductive paste are bonded to the substrate by applying a pressure of 2-20 MPa and a temperature of 100-150° C.

[0032] By adopting the above technical solution, through appropriate pressure and temperature, the first conductive paste and the second conductive paste can be mechanically fixed to the substrate to enhance the quality of the contact interface. This process not only improves the overall conductive performance, but also improves the reliability and stability of the product. Reasonable process control will ensure the consistency and high pass rate of the product, providing a solid foundation for subsequent applications; and it can reduce additional curing time, improve overall production efficiency, and shorten the manufacturing cycle.

[0033] In a specific embodiment, in S7, the polymer layer is dissolved using water at room temperature.

[0034] By adopting the above technical solution, the polymer layer is treated by dissolving in water at room temperature, and the environmentally friendly characteristics and wide applicability of water as a solvent are utilized to avoid the use of organic solvents, reduce the risk of environmental pollution, and meet the requirements of sustainable development. In addition, the dissolution process is simple and easy to control, does not require complex equipment, has strong adaptability, and is easy to use in different production environments. It can also save energy and material costs, improve material utilization through an efficient dissolution process, and reduce overall production costs.

[0035] In a specific implementation manner, in S8, the first conductive paste and the second conductive paste are sintered at a high temperature of 500-1000°C.

[0036] By adopting the above technical scheme, high-temperature sintering promotes the densification of the first conductive paste and the second conductive paste, which can significantly improve the conductivity and ensure the high performance of the material in electrical applications. Under high temperature, the components in the two pastes undergo physical and chemical reactions to achieve mutual cross-linking and sintering, ensuring good adhesion between layers, enhancing interface strength, and improving the stability and durability of the overall structure. It can effectively improve the conductivity, structural stability and adhesion of the conductive paste and optimize the performance of the final product.

[0037] In a specific embodiment, the substrate is one of a single crystal silicon substrate, a polycrystalline silicon substrate, a perovskite substrate, a glass substrate, and a plastic substrate.

[0038] By adopting the above technical solutions, these substrates have excellent mechanical strength, can withstand certain physical pressure and environmental influences in practical applications, ensure the durability of the product, and can effectively absorb and convert light in optoelectronic applications. They are suitable for solar cells and other optoelectronic devices, and can be processed by a variety of processing technologies, providing flexible process options to meet different production needs.

[0039] In a specific implementation manner, the material of the first mold and the second mold is one of single crystal silicon, polycrystalline silicon, copper, nickel, copper-nickel alloy, nickel-iron alloy, iron-aluminum alloy, and aluminum alloy.

[0040] By adopting the above technical scheme, the molds made of the above materials have good wear resistance, can maintain their shape in high-cycle production, reduce wear and extend the service life of the mold; these materials can achieve good molding effects in mold making, ensure that the product surface is smooth and the dimensional accuracy is high, and are suitable for various precision processing needs.

[0041] A photovoltaic cell comprises the electrode grid lines prepared by the preparation method described above.

[0042] By adopting the above technical scheme, the photovoltaic cell with electrode grid lines obtained by applying this preparation method shows significant advantages in conductivity, production efficiency, environmental protection and structural stability. The combined structure of the first conductive paste and the second conductive paste ensures good conductivity of the electrode grid lines. The second conductive paste provides low contact resistance on the contact surface of the battery, thereby improving the current collection efficiency. The parasitic resistance between the electrode grid lines is effectively reduced by the precisely designed electrode pattern and opening width, further improving the energy conversion efficiency of the photovoltaic cell. The method integrates multiple steps by mold stamping and transfer printing, and can achieve high-resolution electrode pattern manufacturing. The good electrode adhesion and environmental resistance make the battery more stable in long-term use, extend the service life, and ensure the accuracy and repeatability of the electrode structure, meeting the strict requirements of optoelectronic devices on electrode shape and size. By controlling the structure of the electrode grid lines, the light absorption efficiency can be improved to ensure that more photons are effectively converted into electrical energy.

[0043] In a specific possible implementation manner, the electrode grid line includes a first conductive layer formed by the first conductive paste and a second conductive layer formed by the second conductive paste, the first conductive layer and the second conductive layer share the same bottom surface, and the height ratio of the first conductive layer to the second conductive layer is 2:1-5:1.

[0044] By adopting the above technical solution, the design of sharing the same bottom surface helps to enhance the bonding force between layers, reduce poor current conduction caused by interface problems between materials, and improve the mechanical strength and long-term stability of the battery; by adjusting the height ratio of the first conductive layer and the second conductive layer, the conductive performance of the electrode can be optimized and the overall production cost can be reduced. The electrode grid line design not only improves the performance of photovoltaic cells, but also provides a guarantee for cost-effectiveness and long-term stability.

[0045] In a specific embodiment, the outer edge shape of the electrode grid line is one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, and a polygon; The outer edge shape of the first conductive layer is an isosceles triangle, an isosceles trapezoid or a symmetrical semi-ellipse, the vertex angle of the isosceles triangle is 20°-60°, the base angle of the isosceles trapezoid is 30°-70°, and the height-to-width ratio of the first conductive layer is 2:1; The outer edge shape of the second conductive layer is an isosceles triangle, the vertex angle of the isosceles triangle is 120°-160°, and the height-to-width ratio of the second conductive layer is 1:2.

[0046] By adopting the above technical solution, the outer edge shape of the electrode grid line is a variety of geometric shapes, which can effectively balance the capture of light and the extraction of current. Different shape designs can affect the effective contact area of ​​the entire electrode, thereby affecting its conductive effect, and the first conductive layer and the second conductive layer adopt a symmetrical graphic design, which can optimize the current flow path and reduce the resistance of the current in the conductive layer, thereby improving the conductivity; the aspect ratio of the first conductive layer is 2:1, which can provide better carrying capacity and current extraction capacity, and is suitable for efficient current conduction. The aspect ratio of the second conductive layer is 1:2, which can effectively increase the contact area of ​​the electrode, while ensuring that the stress distribution of the conductive layer is uniform, further improving the conductive performance; and the first conductive layer and the second conductive layer use the above-mentioned angle design to help reduce the return loss of the current, thereby enhancing the effective conduction of the current.

[0047] In summary, the present application includes at least one of the following beneficial technical effects: the method of the present application adopts a two-layer conductive paste structure (silver paste and aluminum paste), which helps to improve the conductivity, stability and performance of the electrode, so that the electrode exhibits better electrical properties in practical applications, and effectively reduces production costs while maintaining the conductive effect; This process integrates multiple steps together, and through flat-panel coating technology, transfer, water dissolution, drying, high-temperature sintering and other technologies, it realizes the precise coating and curing of the first conductive paste (aluminum paste) and the second conductive paste (silver paste) on the polymer layer (polyvinyl alcohol) carrier, ensuring the accuracy and stability of the electrode pattern, reducing the complex processes in traditional manufacturing methods, improving production efficiency, and reducing manufacturing costs. Through the combination of heat and pressure, good contact and bonding between different materials are ensured, which is beneficial to improving the adhesion of the conductive paste on the substrate, ensuring that the electrode is not easy to fall off during long-term use, enhancing the overall performance of the electrode, and extending the service life of the device; compared with the traditional screen printing method, this application can improve the production rate to a certain extent, meet the needs of large-scale production, and thus improve market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 It is a schematic diagram of the structure and process of the electrode grid line preparation method of the embodiment of the present application.

[0049] Figure 2 It is a schematic diagram used to show the appearance structure of the electrode grid line.

[0050] Explanation of the reference numerals: 1. substrate; 2. polymer layer; 3. first mold; 4. first groove; 5. first conductive paste; 6. second mold; 7. second groove; 8. second conductive paste; 9. substrate; 10. electrode grid line; 11. first conductive layer; 12. second conductive layer. DETAILED DESCRIPTION

[0051] The following is combined with Figure 1-2 This application is described in further detail.

[0052] Embodiment 1 Reference Figure 1 The present application embodiment discloses a method for preparing an electrode grid line 10, comprising the following steps: S1. Provide a substrate 1, and form a polymer layer 2 on the substrate 1. In this process, it is necessary to ensure that the surface of the substrate 1 is clean and flat to ensure the quality of the subsequent coating process, and perform surface treatment on the substrate 1 to enhance the adhesion of the polymer layer 2. The thickness of the substrate 1 is 100-200 μm. In this embodiment, preferably, the thickness of the substrate 1 is 150 μm. The material of the substrate 1 includes but is not limited to one of polyethylene terephthalate (PET), polyimide (PI), polyethylene terephthalate glycol copolymer (PETG), polycarbonate (PC), polypropylene (PP), and polyurethane (PU). In this embodiment, preferably, the material of the substrate 1 is polyimide. Polyimide has good heat resistance and can withstand high temperatures up to 400°C. It has high strength and toughness, provides good structural support and durability, and has good tolerance to a variety of chemical substances and can remain stable in a variety of environments. Before coating, the substrate 1 is subjected to necessary pretreatment, and the pretreatment method includes cleaning, drying and surface activation, and these steps are intended to remove pollutants on the surface of the substrate 1, increase the surface roughness, and improve the adhesion of the polymer layer 2; the specific pretreatment method includes but is not limited to: first, use deionized water, acetone and isopropanol to clean in sequence to remove possible impurities and grease, and then place the substrate 1 in an ultrasonic cleaner for cleaning, the ultrasonic frequency is 40 kHz, and the cleaning time is 15 minutes to ensure that there are no tiny particles remaining on the surface. After cleaning, place the substrate 1 in a hot air circulation device, keep the temperature at 60°C, and dry for 30 minutes to ensure complete drying; A polymer layer 2 is prepared on the cleaned and treated substrate 1. In this embodiment, a flat coating technology is used, but not limited to, to form a polymer layer 2 on the substrate 1. Specifically, a uniform polymer solution is coated on the substrate 1, the uniformity and thickness of the coating are controlled, and a reasonable scraper angle (generally 30°-45°) is set to ensure that the coating is uniform and smooth. After the coating is completed, the substrate 1 is placed in a well-ventilated dry environment, or the volatilization of the solvent is accelerated by heating, including but not limited to drying in a hot air oven, setting the temperature at 90°C - 110°C, and the drying time is 20 to 30 minutes, drying the polymer solution, promoting the cross-linking of the polymer, and forming a polymer layer 2 of 10-12 μm. The thickness of the polymer layer 2 includes but is not limited to 5-20 μm. In this embodiment, preferably, the thickness of the polymer layer 22 is 10 μm. The polymer layer 2 of this thickness can balance strength, flexibility and conductivity, and is suitable for a variety of application requirements. The thin layer design of the polymer layer 2 helps to reduce material waste and makes it suitable for high-density integrated electronic devices or microstructures. In the present embodiment, the glass transition temperature of the polymer layer 22 is 70-100° C. The material of the polymer layer 2 includes but is not limited to a water-soluble polymer material, and the water-soluble polymer material includes but is not limited to polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyethylene glycol (PEG), modified polyvinyl alcohol (MPVA), sodium polyacrylate (PAAS), polyvinyl alcohol-polyacrylic acid (PVA-PAA), polyvinyl alcohol-polyacrylonitrile (PVA-PAN). In the present embodiment, preferably, the water-soluble The polymer material is polyvinyl alcohol, which will change color and become brittle only when heated to above 180°C, providing a wide processing temperature range; polyvinyl alcohol is insoluble in gasoline, kerosene, vegetable oil, benzene, toluene, ethylene dichloride, carbon tetrachloride, acetone, ethyl acetate, methanol, ethylene glycol and other organic solvents; polyvinyl alcohol is easily soluble in water, making the coating and film-forming process more convenient, without the need for complex solvent treatment, and the water-soluble properties make polyvinyl alcohol easy to clean after use, with excellent biocompatibility, friendly to the human body and the environment, and reducing the burden on the environment; Polyvinyl alcohol is a polymer with a large number of strongly hydrophilic -OH groups and has good hydrophilic properties. Its water solubility is largely determined by the degree of polymerization, especially the degree of alcoholysis. The presence of a large number of hydroxyl groups leads to strong hydrogen bonds within and between polyvinyl alcohol molecules, which hinders the solubility of polyvinyl alcohol in water. Therefore, the higher the degree of alcoholysis, the worse the water solubility of polyvinyl alcohol. In addition, the residual acetate radical on the molecular chain of partially alcoholyzed polyvinyl alcohol should be hydrophobic, but its presence can also weaken the hydrogen bonds within and between adjacent molecules. Therefore, the presence of an appropriate amount of acetate radical can improve the water solubility of polyvinyl alcohol. With the increase of acetate radicals, the dissolution endotherm increases, the critical temperature of phase separation decreases, and the solubility at high temperature gradually decreases. Therefore, the factors affecting the water solubility of polyvinyl alcohol are complex. In this embodiment, the water solubility of polyvinyl alcohol can be changed by adjusting the alcoholysis degree of polyvinyl alcohol or performing a blending modification method so that it can be quickly dissolved at room temperature; specifically, the method includes: a. Appropriately adjust the alcoholysis degree of polyvinyl alcohol (i.e., the alcoholysis degree of polyvinyl alcohol). Specifically, in a methanol solution of polyvinyl acetate (containing 1% to 2% water), add an aqueous sodium hydroxide solution to carry out alcoholysis to generate polyvinyl alcohol (refer to reaction formula (1.1)). During the alcoholysis process, water is present in the system, the alkali molar ratio is large, and the reaction formula (1.1) is accelerated. At the same time, under the action of water, the dissociation degree of the alkali is large, the catalytic effect is enhanced, and the ester exchange reaction formula (1.2) is also accelerated. The entire reaction speed is very fast and can be completed in about 1 minute. The characteristics of this wet alcoholysis (high alkali alcoholysis) are fast reaction speed, small equipment size, high production capacity, and continuous alcoholysis process.

[0053] (1.1) (1.2) Specifically, after the polyvinyl acetate methanol solution is heated in a preheater, it is quickly and evenly mixed with the alcoholysis catalyst sodium oxide methanol solution in a static mixer for a mixing time of 0.1 to 0.3 minutes, and then enters a twin-screw extruder alcoholysis machine for alcoholysis at 45 to 75° C. for 0.5 to 4 minutes. The alcoholysis product is washed with an acid-containing solvent and then dried to obtain a partially alcoholysed polyvinyl alcohol product in the form of white granules; In this embodiment, the alcoholysis degree can be adjusted according to actual needs. For example, polyvinyl alcohol with an alcoholysis degree of 80% is used for low-temperature water-soluble at 40°C, and 88% is used for high-temperature water-soluble.

[0054] b. Blending polyvinyl alcohol with other water-soluble polymers or additives can improve its water solubility. Specifically, a hydrophilic polymer or additive (such as polyacrylic acid, polyglycolic acid, etc.) with good compatibility with polyvinyl alcohol is selected. Different blending ratios are designed according to application requirements. The common blending ratio can be between 10% and 50%. Different ratios have a direct impact on water solubility and physical properties. The selected ratio of polyvinyl alcohol and the blending material are melted at high temperature and then cooled to form a blend; thereby, the solubility and dissolution rate of polyvinyl alcohol can be enhanced. By optimizing the blending ratio and selecting an appropriate modifier, the solubility of polyvinyl alcohol can be adjusted to meet specific application requirements; The water dissolution rate of polyvinyl alcohol after alcoholysis or blending can be tested; specifically, the sample is placed in water, its dissolution time is observed and the data is recorded. The mechanical strength, ductility, tensile strength, etc. of polyvinyl alcohol can also be tested to evaluate the effect of blending modification on material properties.

[0055] S2. Provide a first mold 3, and use the hot pressing technology to press a first groove 4 corresponding to the desired electrode pattern on the polymer layer 2 using the first mold 3; in this embodiment, the material of the first mold 3 is one of single crystal silicon, polycrystalline silicon, copper, nickel, copper-nickel alloy, nickel-iron alloy, iron-aluminum alloy, and aluminum alloy; in this embodiment, the groove depth of the first groove 4 is 10±2μm, and the aspect ratio of the first groove 4 is 2:1; In the present embodiment, the opening width of the electrode pattern of the polymer layer 2 is 3-10 μm, and the aspect ratio is 2:1, that is, the notch width of the first groove 4 is 3-10 μm, and the aspect ratio is 2:1; by using the design that the thickness of the polymer layer 2 is in the range of 5-20 μm, the width of the electrode patterned opening is in the range of 3-10 μm, and the aspect ratio is 2:1, the above dimensions can take into account the subsequent filling efficiency of the conductive paste and the requirements for the dimensional accuracy of the electrode grid line 10, and the narrower opening width helps to reduce the parasitic resistance between the electrode grid lines 10 and improve the current collection efficiency of the battery. At the same time, within the width range, it can also ensure that the conductive paste can be fully and evenly filled into the opening to avoid the generation of voids or defects. By accurately controlling the thickness of the polymer layer 2 and the width of the patterned opening, the dimensional accuracy of the electrode grid line 10 can be significantly improved, which helps to reduce performance fluctuations and defective product rates caused by dimensional deviations; In this embodiment, the first groove 4 corresponding to the electrode pattern is formed by hot pressing the polymer layer 2 by a hot press machine, but is not limited thereto. In this embodiment, the hot pressing temperature of the polymer layer 2 is 90-150° C. Preferably, the best hot pressing molding conditions are: hot pressing temperature of 130° C., hot pressing pressure of 10 MPa, and hot pressing time of 2 min. Under these conditions, the first groove 4 can be well hot pressed. Specifically, the dried polymer layer 2 is placed on a hot press. According to the characteristics of the polymer layer 2 and the accuracy of the required electrode pattern, the temperature of the hot press is set to 130°C, the pressure is set to 10MPa and the time is set to 2min. The temperature can soften the polymer layer 22, the pressure can ensure that the pattern of the first mold 3 on the hot press can be fully high-precision embossed, and the time can ensure that the details of the pattern are accurately replicated. The dried polymer layer 2 is placed on the heating plate of the hot press, and then the first mold 3 is aligned and pressed down. The heating plate is heated to 130°C. The first mold 3 is placed on the heating plate at 100°C. MPa pressure, press the polymer layer 2 into the first mold 3 and press out a first groove 4 with a depth of 10um and a width of 5um corresponding to the desired electrode pattern. Hot press for 2 minutes to ensure that the polymer layer 2 is fully formed under high temperature and high pressure. After the hot pressing, the first mold 3 and the polymer layer 2 need to be cooled to room temperature. This cooling process allows the polymer layer 2 to maintain its shape in the first mold 3, so that the shape and size of the first groove 4 are stabilized. After the cooling is completed, carefully remove the first mold 3 from the polymer layer 2. The pattern of the first groove 4 is clearly visible and matches the desired electrode pattern. Carefully check to confirm whether the size and shape of the first groove 4 meet the requirements of the micron or even nanometer electrode pattern.

[0056] In this process, the hot pressing temperature range is above the glass transition temperature of polyvinyl alcohol and below its melting point, which avoids discoloration and embrittlement of the polymer 2 during the hot pressing process, thereby ensuring the machinability, stability and uniformity of the material; under the above-mentioned optimal hot pressing molding conditions, the polymer layer 2 can be better shaped to form a precise shape of the first groove 4, thereby improving the processing accuracy and quality of the finished product, and by controlling the hot pressing temperature within a safe range, the thermal stress caused by excessive temperature is reduced, thereby reducing thermal damage to the material.

[0057] The shape and size of the first groove 4 correspond to the electrode grid line 10. In actual operation, the size and shape of the electrode grid line 10 to be transferred are controlled to reduce the ohmic loss of the electrode grid line 10. The longitudinal cross-sectional shape of the first groove 4 includes but is not limited to one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, and a polygon. In the present embodiment, preferably, the longitudinal cross-sectional shape of the first groove 4 is a triangle, a trapezoid, or a semi-ellipse. The above longitudinal cross-sectional design helps to change the incident and refraction paths of light, can better capture and guide light, can effectively reduce the reflection loss of light, so that more light is absorbed by the semiconductor material and converted into electrical energy, thereby improving the photoelectric conversion efficiency.

[0058] S3, using a flat coating technique, applying the first conductive paste 5 on the polymer layer 2, so that the first conductive paste 5 fills the first groove 4, and scraping off the excess first conductive paste 5; Specifically, on the polymer layer 2 where the first groove 4 has been formed, the first conductive paste 5 is evenly applied by a flat coating technology, a suitable first conductive paste 5 is selected, and a flat coater or a scraping tool is used for coating, and the first conductive paste 5 is evenly applied on the polymer layer 2, and is moved along the surface of the polymer layer 2 at a steady speed with appropriate pressure to ensure that the first conductive paste 5 is squeezed into the first groove 4, and that the material can fully fill all the gaps in the first groove 4 and cover the entire surface. After coating, a scraper or other tool is used to scrape off the excess first conductive paste 5 on the surface to ensure that the first conductive paste 5 in the first groove 4 is flat and tightly combined with the polymer layer 2; The first conductive paste 5 includes but is not limited to one of aluminum paste, copper paste, chromium paste, tin paste, indium paste, nickel paste, titanium paste, and tantalum paste; preferably, the first conductive paste 5 is aluminum paste. Aluminum has good conductivity and can meet the conductivity requirements of many electronic devices and circuits. Compared with other metal pastes, aluminum paste has a lower cost, and it is more economically feasible to manufacture and use aluminum paste, especially in large-scale applications. Aluminum paste can be widely used in conductive coatings, flexible electronic components, solar cells, PCBs (printed circuit boards) and other fields.

[0059] S4, providing a second mold 6, using the hot pressing technology, using the second mold 6 to press out a second groove 7 on the first conductive paste 5, and drying the first conductive paste 5; in this embodiment, the material of the second mold 6 is one of single crystal silicon, polycrystalline silicon, copper, nickel, copper-nickel alloy, nickel-iron alloy, iron-aluminum alloy, and aluminum alloy; In the present embodiment, the second groove 7 is formed by hot pressing the first conductive paste 5 with a hot press, but is not limited thereto. In the present embodiment, the hot pressing temperature of the first conductive paste 5 is 90-150°C. Preferably, the best hot pressing molding conditions are: the hot pressing temperature is 130°C, the hot pressing pressure is 10MPa, and the hot pressing time is 2min. Under this condition, the second groove 7 can be well hot pressed. In the present embodiment, the groove depth of the second groove 7 is 2-5um, the width of the second groove 7 is the same as the width of the first groove 4, and the height ratio of the first groove 4 to the second groove 7 is 2:1-5:1. Preferably, the height ratio of the first groove 4 to the second groove 7 is 3:1. The design of the same width ensures good docking between the two conductive layers, which helps to improve the conductivity and stability of the electrode. Specifically, the temperature of the hot press is set to 130°C, the pressure is 10MPa and the time is 2min. The temperature can soften the first conductive paste 5, the pressure can ensure that the pattern of the second mold 6 on the hot press can be fully and accurately embossed, and the time can ensure that the details of the pattern are accurately replicated. The dried polymer layer 2 and the first conductive paste 5 are placed on the heating plate of the hot press, and then the second mold 6 is aligned and pressed down. The heating plate is heated to 130°C, and the second mold 6 is placed on the heating plate at 10MPa. The first conductive paste 5 is pressed into the mold 6 at a pressure of 100 MPa to form a second groove 7 pattern with a depth of 2-5 μm and a width of 5 μm. The mold 6 is hot-pressed for 2 minutes to scrape off the first conductive paste 5 overflowing on the surface of the polymer layer 2. After the hot-pressing is completed, the first conductive paste 5 is dried at 100-200° C., preferably, the first conductive paste 5 is dried at 130° C. This process allows the first conductive paste 5 to maintain its shape in the second mold 6, so that the shape and size of the second groove 7 are stabilized. After the drying is completed, the second mold 6 is removed, and the pattern of the second groove 7 is clearly visible. Carefully check to confirm whether the size and shape of the second groove 7 meet the requirements of the micron-level or even nano-level electrode pattern. Under the above-mentioned optimal hot pressing molding conditions, the first conductive paste 5 can be better shaped to form a precise second groove 7 shape, thereby improving processing accuracy and finished product quality. By controlling the hot pressing temperature within a safe range, the thermal stress caused by excessive temperature is reduced, thereby reducing thermal damage to the material.

[0060] S5, using a flat coating technique, applying the second conductive paste 8 on the first conductive paste 5, so that the second conductive paste 8 fills the second groove 7, and scraping off excess second conductive paste 8; Specifically, on the first conductive paste 5 where the second groove 7 has been formed, the second conductive paste 8 is evenly applied by a flat coating technique, a suitable second conductive paste 8 is selected, and a flat coating machine or a scraping tool is used for coating, and the second conductive paste 8 is evenly applied on the first conductive paste 5 to ensure that the material can fully fill all the gaps in the second groove 7 and cover the entire surface. After coating, a scraper or other tool is used to scrape off the excess second conductive paste 8 on the surface to ensure that the second conductive paste 8 in the second groove 7 is flat and tightly combined with the first conductive paste 5; In this embodiment, the contact resistance of the second conductive paste 8 is smaller than the contact resistance of the first conductive paste 5, and the electrical conductivity of the second conductive paste 8 is greater than the electrical conductivity of the first conductive paste 5; the second conductive paste 8 is used as a material that will be in direct contact with the substrate 9 later. The low contact resistance and high electrical conductivity of the second conductive paste 8 can improve the connection performance between the substrate 9 and the electrode, ensuring that the current can flow smoothly through each contact point. Good electrical properties help to improve the overall reliability of the device and avoid performance degradation or failure due to poor contact.

[0061] Preferably, the second conductive paste 8 includes but is not limited to silver paste; by limiting the silver paste to the area in contact with the substrate 9, the amount of silver paste can be significantly reduced, and the conductive efficiency of the entire circuit can still be guaranteed. In contrast, the first conductive paste 5 can use materials with better conductive properties to compensate for part of the performance; the present application combines the second conductive paste 8 silver paste with other lower-cost first conductive paste 5 aluminum paste, which can not only reduce production costs, but also bring technical advantages in improving product performance, ensuring conductive efficiency and improving mechanical strength. The components of the silver paste include an adhesive. The adhesive in the silver paste is non-reactive and is a phenolic resin or an epoxy resin. The adhesive is used to enhance the bonding between the particles of the silver paste. In this embodiment, the shear strength of the adhesive is 10-30 MPa, and it has excellent bonding performance and chemical resistance. The design of the adhesive can effectively enhance the bonding force between the silver particles in the silver paste, thereby reducing the interruption of the conductive path in the silver paste and improving the conductivity. The polymer layer 2 of polyvinyl alcohol is incompatible with the adhesive of the silver paste and is non-reactive; the non-reactivity ensures that no chemical changes or degradation will occur between the polyvinyl alcohol and the silver paste, maintaining the stability of their respective performance, ensuring that each material performs optimally in its intended application, avoiding mutual influence, and allowing the polymer layer 2 to be easily removed through water solubility after processing without affecting the performance of the silver paste.

[0062] S6, providing a substrate 9, covering the polymer layer 2 on the substrate 9, the polymer layer 2, the first conductive paste 5 and the second conductive paste 8 are transferred to the substrate 9 at a certain temperature and pressure, and the second conductive paste 8 is dried and shaped at the same time to enhance the adhesion to the surface of the substrate 9; in this process, including but not limited to the polymer layer 2, the first conductive paste 5 and the second conductive paste 8 are bonded and attached to the substrate 9 by a high temperature of 100-150°C and a pressure of 2-20MPa. In this embodiment, preferably, the best hot pressing transfer conditions are: the hot pressing temperature is 130°C, the hot pressing pressure is 10 MPa, and the hot pressing time is 8min. Under this condition, the polymer layer 2, the first conductive paste 5 and the second conductive paste 8 can be well adhered to the substrate 9. In this process, the second conductive paste 8 is dried and shaped at the same time to enhance the adhesion to the surface of the substrate 9; the morphology of the first conductive paste 5 and the second conductive paste 8 is complete and without deformation, and the polymer layer 2 and the substrate 1 can be well peeled off; Specifically, clean the surface of the substrate 9 to remove any contaminants or particles, ensure that the surface of the substrate 9 is clean and flat, cover the polymer layer 2 coated with the first conductive paste 5 and the second conductive paste 8 on the substrate 9, accurately align the substrate 9, ensure that the first conductive paste 5 and the second conductive paste 8 are aligned with the position on the substrate 9, and use an alignment tool or a visual alignment system to improve the alignment accuracy. Gently place it on the substrate 9 to ensure that each part of the second conductive paste 8 is in close contact with the surface of the substrate 9. Apply a pressure of 10 MPa and a hot pressing temperature of 130°C to press the polymer layer 2, the first conductive paste 5 and the second conductive paste 8 onto the substrate 9. The pressure needs to be evenly distributed to ensure that the first conductive paste 5 and the second conductive paste 8 are completely attached to form a clear pattern. This step requires ensuring that the pressure is evenly applied to ensure the accurate transfer of the first conductive paste 5 and the second conductive paste 8. After applying the pressure, maintain the hot pressing between the substrate 9 for 8 minutes to ensure that the first conductive paste 5 and the second conductive paste 8 are fully in contact and adhere to the substrate 9. In this embodiment, the adhesive can also enhance the bonding between the silver paste particles of the second conductive paste 8 and the substrate 9. After hot pressing transfer, the first conductive paste 5, the second conductive paste 8 and the polymer layer 2 will be tightly adhered to the substrate 9, and the other side can be easily peeled off from the base 1. The adhesive in the silver paste can promote the adhesion between the silver paste particles and the substrate 9, improve the bonding strength between the second conductive paste 8 and the substrate 9, further optimize the conductive performance, and at the same time improve the overall durability and reliability.

[0063] S7, the substrate 1 and the polymer layer 2 are peeled off, and the polymer layer 2 is dissolved, and the first conductive paste 5 and the second conductive paste 8 are left adhering to the substrate 9; the substrate 9 includes but is not limited to one of a single crystal silicon substrate 9, a polycrystalline silicon substrate 9, a perovskite substrate 9, a glass substrate 9, and a plastic substrate 9. In this embodiment, preferably, the substrate 9 is a polycrystalline silicon substrate 9. The polycrystalline silicon substrate 9 has good electronic conductivity and stability, and has good thermal stability and thermal conductivity, and is suitable for the manufacture of various electronic devices, and can be used in the photovoltaic cell applied in this application; Specifically, after the transfer work is completed, the substrate 1 and the polymer layer 2 are first peeled off, and then the polymer layer 2 is dissolved using water at room temperature. In this embodiment, the temperature of the water at room temperature includes but is not limited to 20-25°C. After the substrate 11 is peeled off, first, the polymer layer 2 is immersed in a container filled with water at room temperature. The water temperature should be maintained at room temperature of 20-25°C to avoid thermal damage to the first conductive paste 5, the second conductive paste 8 or the substrate 9. During the immersion process, the polymer layer 2 will gradually dissolve in the water. In order to ensure that the polymer layer 2 is completely dissolved, the water can be stirred appropriately or the water temperature can be increased to promote the uniform dissolution process. The time of this process depends on the thickness and material properties of the polymer layer 2. During this period, the dissolution of the polymer layer 2 needs to be checked regularly to ensure that it is completely dissolved. When the polymer layer 2 is completely dissolved, the patterns of the first conductive paste 5 and the second conductive paste 8 on the surface of the polymer layer 2 will be completely retained on the substrate 9; In order to further ensure the adhesion and stability of the first conductive paste 5 and the second conductive paste 8, the surface of the substrate 9 can be rinsed with clean water to remove the tiny fragments of the polymer layer 2 that may remain. Finally, the transferred substrate 9 is dried in the air or by other methods to prepare for the next step of processing.

[0064] S8, sintering the first conductive paste 5 and the second conductive paste 8 to form the electrode grid line 10; in this embodiment, including but not limited to sintering the first conductive paste 5 and the second conductive paste 8 at a high temperature of 500-1000° C.; Specifically, the substrate 9 coated with the first conductive paste 5 and the second conductive paste 8 is placed in a heating furnace for high-temperature sintering at 500-1000°C. The temperature and time of the sintering process should be set according to the first conductive paste 5 and the second conductive paste 8 to ensure that it can be fully sintered at high temperature without damaging the substrate 9. The sintering time should be set according to the characteristics of the first conductive paste 5 and the second conductive paste 8 to ensure that the material has enough time to complete chemical reactions or physical changes at high temperatures to achieve optimal conductivity and adhesion. After sintering, the substrate 9 is allowed to cool naturally to room temperature to avoid thermal stress from damaging the electrode grid lines 10. The sintered electrode grid lines 10 are checked to ensure that their patterns are clear and well adhered. Check whether there is poor conductivity, defects or falling off to ensure that the quality of the electrode grid lines 10 meets the design requirements. During this process, if necessary, cleaning is performed to remove any residues or contaminants from the sintering process, and electrical performance testing can also be performed to verify whether the conductivity of the electrode grid line 10 meets the specifications and confirm its performance in actual applications.

[0065] The method of the present application adopts a two-layer conductive paste structure (a first conductive paste 5 and a second conductive paste 8), which helps to improve the conductivity, stability and performance of the electrode, so that the electrode exhibits better electrical characteristics in practical applications, and can effectively reduce production costs; by using a mold to press a groove on the polymer layer 2, the pressure and temperature during the transfer process ensure that the first conductive paste 5 and the second conductive paste 8 are accurately transferred and attached to the substrate 9, the accuracy of the electrode pattern is maintained, and high-resolution and high-precision electrode pattern manufacturing is achieved, ensuring the accuracy and repeatability of the electrode structure, and meeting the strict requirements of optoelectronic devices on electrode shape and size; This process integrates multiple steps together. Through flat coating technology, transfer, water dissolution, drying, high-temperature sintering and other technologies, the first conductive paste 5 (aluminum paste) and the second conductive paste 8 (silver paste) are accurately applied and cured on the polymer layer 2 (polyvinyl alcohol) carrier, ensuring the accuracy and stability of the electrode pattern, reducing the complex processes in the traditional manufacturing method, improving production efficiency, and reducing manufacturing costs. Through the combination of heat and pressure, good contact and bonding between different materials are ensured, which is beneficial to improving the adhesion of the conductive paste on the substrate 9, ensuring that the electrode is not easy to fall off during long-term use, enhancing the overall performance of the electrode, and extending the service life of the device; and the use of the polymer layer 2 can be removed by dissolution in subsequent steps, which helps to reduce the waste generated in the traditional process and reduce environmental pollution; compared with the traditional screen printing method, the present application can improve the production rate to a certain extent, meet the needs of large-scale production, and thus improve market competitiveness.

[0066] Embodiment 2 Reference Figure 2 , the embodiment of the present application provides a photovoltaic cell, comprising an electrode grid line 10 prepared by the preparation method described in the first embodiment; The electrode grid line 10 includes a first conductive layer 11 formed by a first conductive paste 5 and a second conductive layer 12 formed by a second conductive paste 8. The first conductive layer 11 and the second conductive layer 12 share the same bottom surface, and the height ratio of the first conductive layer 11 to the second conductive layer 12 is 2:1-5:1. The design of sharing the same bottom surface helps to enhance the bonding force between layers, reduce poor current conduction caused by interface problems between materials, and improve the mechanical strength and long-term stability of the battery. Since the second conductive layer 12 is a conductive layer in direct contact with the substrate 9, the material of the second conductive layer 12 is silver paste, and the material of the first conductive layer 11 is aluminum paste. The aluminum paste as the first conductive layer 11 provides a cost-effective conductive solution, while the silver paste as the second conductive layer 12 promotes higher conductivity. Since the conductivity of silver is better than that of aluminum, by adjusting the height ratio of the two layers (2:1-5:1), the flow path of the current can be optimized, the current transmission efficiency can be improved, and the overall conductive performance of the electrode can be improved. Compared with the single use of high-cost materials (such as silver paste), this layered design can reduce the use of silver paste without sacrificing electrode performance, thereby effectively reducing production costs. The electrode grid line 10 design not only improves the performance of photovoltaic cells, but also provides a guarantee for cost-effectiveness and long-term stability.

[0067] In this embodiment, the height of the electrode grid line 10 includes but is not limited to 10±2um, and the aspect ratio of the electrode grid line 10 is 2:1; the outer edge shape of the electrode grid line 10 includes but is not limited to one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, and a polygon; the outer edge shape of the electrode grid line 10 is a variety of geometric shapes, which can effectively balance the capture of light and the derivation of current. Different shape designs can affect the effective contact area of ​​the entire electrode, thereby affecting its conductive effect; The outer edge shape of the first conductive layer 11 is an isosceles triangle, an isosceles trapezoid or a symmetrical semi-ellipse, the vertex angle of the isosceles triangle is 20°-60°, the base angle of the isosceles trapezoid is 30°-70°, and the aspect ratio of the first conductive layer 11 is 2:1; the outer edge shape of the second conductive layer 12 is an isosceles triangle, the vertex angle of the isosceles triangle is 120°-160°, and the aspect ratio of the second conductive layer 12 is 1:2; The first conductive layer 11 and the second conductive layer 12 adopt a symmetrical graphic design, which can optimize the current flow path and reduce the resistance of the current in the conductive layer, thereby improving the conductivity; under the premise that the height ratio of the first conductive layer 11 and the second conductive layer 12 is 2:1-5:1, the aspect ratio of the first conductive layer 11 is 2:1, which can provide better carrying capacity and current extraction capacity, and is suitable for efficient current conduction. The aspect ratio of the second conductive layer 12 is 1:2, which can effectively increase the contact area of ​​the electrode, while ensuring that the stress distribution of the conductive layer is uniform, further improving the conductivity; and the first conductive layer 11 and the second conductive layer 12 use the above-mentioned angle design, which helps to reduce the return loss of the current, thereby enhancing the effective conduction of the current; The photovoltaic cell with the electrode grid lines 10 obtained by applying this preparation method has shown significant advantages in terms of conductivity, production efficiency, environmental protection and structural stability, which can effectively reduce the manufacturing cost of photovoltaic cells and improve production efficiency, and is expected to be widely used in the photovoltaic cell industry; the combination structure of the first conductive paste 5 (aluminum paste) and the second conductive paste 8 (silver paste) is adopted to ensure the good conductivity of the electrode grid lines 10, and the second conductive paste 8 provides low contact resistance on the contact surface of the battery, thereby improving the current collection efficiency. The parasitic resistance between the electrode grid lines 10 is effectively reduced by the precisely designed electrode pattern and opening width, further improving the energy conversion efficiency of the photovoltaic cell; the technical solution of preparing the electrode grid lines 10 by mixing aluminum and silver paste is highly innovative and practical, and is expected to promote the development of photovoltaic cell electrode grid line 10 printing technology, bringing new development opportunities to the photovoltaic industry; In addition, this method integrates multiple steps by means of mold imprinting and transfer, and can achieve high-resolution electrode pattern manufacturing. Good electrode adhesion and environmental resistance make the battery more stable in long-term use, extend the service life, and ensure the accuracy and repeatability of the electrode structure, meeting the strict requirements of optoelectronic devices on electrode shape and size; by controlling the structure of the electrode grid line 10, the light absorption efficiency can be improved to ensure that more photons are effectively converted into electrical energy.

[0068] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing an electrode grid line, characterized in that: The following steps are involved: S1, providing a substrate, and forming a polymer layer on the substrate; S2, providing a first mold, and using the first mold to press a first groove corresponding to a desired electrode pattern on the polymer layer; S3, applying a first conductive paste on the polymer layer, so that the first conductive paste fills the first groove, and scraping off excess of the first conductive paste; S4, providing a second mold, using the second mold to press a second groove on the first conductive paste, and drying the first conductive paste; S5. Apply the second conductive paste on the first conductive paste so that the second conductive paste fills the second groove, and scrape off the excess second conductive paste; S6. Provide a substrate, cover the polymer layer on the substrate, and transfer the polymer layer, the first conductive paste and the second conductive paste to the substrate at a certain temperature and pressure. The second conductive paste is dried and fixed at the same time to enhance the adhesion to the surface of the substrate; S7. Peel off the substrate and the polymer layer, and dissolve the polymer layer, leaving the first conductive paste and the second conductive paste adhered to the substrate; S8. Sinter the first conductive paste and the second conductive paste to form the electrode grid line.

2. The method for preparing an electrode grid line according to claim 1, characterized in that: The thickness of the polymer layer is 5-20 μm, and the opening width of the electrode pattern is 3-10 μm.

3. The method for preparing an electrode grid line according to claim 2, characterized in that: The glass transition temperature of the polymer layer is 70-100° C., and the material of the polymer layer is a water-soluble polymer material.

4. The method for preparing an electrode grid line according to claim 3, characterized in that: The water-soluble polymer material is one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, and polyvinyl alcohol-polyacrylonitrile.

5. The method for preparing an electrode grid line according to claim 1, characterized in that: The contact resistance of the second conductive paste is smaller than the contact resistance of the first conductive paste, and the conductivity of the second conductive paste is greater than the conductivity of the first conductive paste.

6. The method for preparing an electrode grid line according to claim 5, characterized in that: The second conductive paste is silver paste, and the first conductive paste is one of aluminum paste, copper paste, chromium paste, tin paste, indium paste, nickel paste, titanium paste, and tantalum paste.

7. The method for preparing an electrode grid line according to claim 6, characterized in that: The silver paste comprises a binder, and the binder is a phenolic resin or an epoxy resin.

8. The method for preparing an electrode grid line according to claim 1, characterized in that: The width of the first groove is the same as the width of the second groove, and the ratio of the height of the first groove to the height of the second groove is 2:1-5:

1.

9. The method for preparing an electrode grid line according to claim 1, characterized in that: The material of the substrate includes one of polyethylene terephthalate, polyimide, polyethylene terephthalate copolymer, polycarbonate, polypropylene, and polyurethane, and the thickness of the substrate is 100-200 μm.

10. The method for preparing an electrode grid line according to claim 1, characterized in that: The longitudinal cross-sectional shape of the first groove and the second groove is one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, and a polygon.

11. The method for preparing an electrode grid line according to claim 1, characterized in that: The first groove and the second groove are formed by hot pressing at a temperature of 90-150°C.

12. The method for preparing an electrode grid line according to claim 1, characterized in that: In S4, after the second groove is pressed out, the first conductive paste is dried at a temperature of 100-200° C.

13. The method for preparing an electrode grid line according to claim 1, characterized in that: In S6, the first conductive paste and the second conductive paste are bonded to the substrate by applying a pressure of 2-20 MPa and a temperature of 100-150° C.

14. The method for preparing an electrode grid line according to claim 1, characterized in that: In S7, the polymer layer is dissolved using water at room temperature.

15. The method for preparing an electrode grid line according to claim 1, characterized in that: In the S8, the first conductive paste and the second conductive paste are sintered at a high temperature of 500-1000°C.

16. The method for preparing an electrode grid line according to claim 1, characterized in that: The substrate is one of a single crystal silicon substrate, a polycrystalline silicon substrate, a perovskite substrate, a glass substrate, and a plastic substrate.

17. The method for preparing an electrode grid line according to claim 1, characterized in that: The material of the first mold and the second mold is one of single crystal silicon, polycrystalline silicon, copper, nickel, copper-nickel alloy, nickel-iron alloy, iron-aluminum alloy, and aluminum alloy.

18. A photovoltaic cell, characterized in that: Including the electrode grid line prepared by the preparation method according to any one of claims 1 to 17.

19. The photovoltaic cell according to claim 18, characterized in that: The electrode grid line includes a first conductive layer formed by the first conductive paste and a second conductive layer formed by the second conductive paste. The first conductive layer and the second conductive layer share the same bottom surface. The height ratio of the first conductive layer to the second conductive layer is 2:1-5:

1.

20. The photovoltaic cell according to claim 19, characterized in that: The outer edge shape of the electrode grid line is one of a triangle, a trapezoid, a rectangle, a rhombus, a semicircle, and a polygon; The outer edge shape of the first conductive layer is an isosceles triangle, an isosceles trapezoid or a symmetrical semi-ellipse, the vertex angle of the isosceles triangle is 20°-60°, the base angle of the isosceles trapezoid is 30°-70°, and the height-to-width ratio of the first conductive layer is 2:1; The outer edge shape of the second conductive layer is an isosceles triangle, the vertex angle of the isosceles triangle is 120°-160°, and the height-to-width ratio of the second conductive layer is 1:2.

Citation Information

Cited By

  • Electrode grid line preparation method and photovoltaic cell

    CN120417541A

  • A photovoltaic electrode composite grid line and a preparation method and application thereof

    CN122971043A